Let's evaluate the left-hand side and the right-hand side of the expression separately to determine which operator can be used.
Left-hand side:
\(-6 + 3 \cdot 5\)
First, compute \(3 \cdot 5\):
\(3 \cdot 5 = 15\)
Now, calculate \(-6 + 15\):
\(-6 + 15 = 9\)
So the left-hand side equals \(9\).
Right-hand side:
\(16 - \sqrt{16} + 32 \div 8\)
First, calculate the square root and division:
\(\sqrt{16} = 4\)
\(32 \div 8 = 4\)
Now substitute these back into the expression:
\(16 - 4 + 4\)
Now perform the operations from left to right:
\(16 - 4 = 12\)
Then add \(4\):
\(12 + 4 = 16\)
So the right-hand side equals \(16\).
Now we have:
Left side = \(9\)
Right side = \(16\)
Now we can compare: \(9\) ______ \(16\)
We see that \(9 < 16\).
The operator that makes the statement true is:
< (less than)